2014
DOI: 10.1177/1534735414563977
|View full text |Cite
|
Sign up to set email alerts
|

Use and Safety of Intratumoral Application of European Mistletoe (Viscum album L) Preparations in Oncology

Abstract: Background. Intratumoral (IT) injection of European mistletoe (Viscum album L) preparations might induce local tumor response through combined cytotoxic and immunomodulatory actions of the preparations. Although promising in vitro and in vivo data, along with clinical case studies suggest the need for validation of this hypothesis in prospective trials, the safety of IT mistletoe injections has yet to be thoroughly assessed. Methods. The present study summarizes the practice and safety of off-label IT mistleto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 43 publications
1
29
1
1
Order By: Relevance
“…For all other SOCs, the patient’s proportion was higher in the control group ( Figure 2 ). No serious AEs and serious adverse reactions (ICH) [ 40 ] were documented for the total study cohort. No deaths from study-drug toxic effects were reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For all other SOCs, the patient’s proportion was higher in the control group ( Figure 2 ). No serious AEs and serious adverse reactions (ICH) [ 40 ] were documented for the total study cohort. No deaths from study-drug toxic effects were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, add-on VA maintained ICI-induced toxicity profile in patients with advanced and metastasized lung cancer and melanoma [ 36 , 37 ]. Add-on VA therapy has been reported to entail a sound safety profile with no serious side effects [ 35 , 38 , 39 , 40 ]. We hypothesize that addition of VA therapy in the present study would not increase the known side effects of targeted treatment and might even reduce them.…”
Section: Introductionmentioning
confidence: 99%
“…With regards to adverse effects the safety profile of VA has indicated that subcutaneous (s.c.) and intravenous (i.v.) applications of VA in cancer were safe with no serious AEs [30][31][32][33]. A meta-analysis of clinical studies that applied VA Iscador preparations concluded that it might have beneficial effects in psychosomatic self-regulation in addition to short-term quality of life-improving effects in cancer patients [34].…”
Section: Introductionmentioning
confidence: 99%
“…In der Klinik entspräche dies am ehesten der intratumoralen, intrapleuralen und auch intravesikalen Applikation. Diese Applikationsformen liegen ebenso wie die Infusion außerhalb der arzneimittelrechtlichen Zulassung [31], es liegen aber wissenschaftliche Daten aus klinischen Studien vor [32][33][34][35]. Die intravesikale Instillation von Mistelextrakt mit dem Ziel der Rezidivprophylaxe beim oberflächli-chen Harnblasenkarzinom hatte in ersten Untersuchungen vergleichbare Effekte zur üblicherweise mit dem Immunmodulator BCG (Bacillus Calmette-Guérin) oder dem Zytostatikum Mitomycin erfolgenden Instillationstherapie gezeigt [34] und wird daher z. Zt.…”
Section: Introductionunclassified